مصادر الضغوط المهنية لدى معلمي التربية المهنية في الأردن واستراتيجيات التعامل معها من وجهة نظرهم في ضوء بعض المتغيرات - بدران، بلال عمر (جامعة الأزهر - كلية التربية, 2017)
هدفت الدراسة معرفة مصادر الضغوط المهنية لدى معلمي التربية المهنية في الأردن، واستراتيجيات التعامل معها، لعينة قوامها(250) معلم ومعلمة تربية مهنية من سلطات تعليمية متنوعة شملت وزارة التربية والتعليم، وكالة الغوث، والقطاع الخاص. تكونت أداة الدراسة من استبانة من جزأين: الأول لتحديد مصادر الضغوط المهنية لدى معلمي التربية المهنية، والثاني لتعرف استراتيجيات التوافق للضغوط المهنية التي يستخدمها المعلمون. للإجابة عن أسئلة الدراسة تم استخدام المتوسطات الحسابية والانحرافات المعيارية والنسب المئوية، بالإضافة إلى تحليل التباين الأحادي(ANOVA)، واختبار توكي(Tukey).بينت النتائج أن اهم مصادر الضغوط المهنية تراوحت بين الأداء السيئ للطلبة على الامتحانات، والتخطيط اليومي، وتصحيح الاختبارات، والضوضاء أثناء التدريس، وعدم توفر الدعم المادي، وقلة فرص التطور الوظيفي، كما بينت النتائج أن أهم الاستراتيجيات لا تختلف باختلاف السلطة المشرفة على المعلمين.
This study investigated the sources of vocational stress among the vocational teachers in Jordan and their compatibility strategies. The sample of the study consisted of (250) male and female vocational teachers from different educational authorities included: The Ministry of Education, The United Nations Relief and Works Agency (UNRWA), and the Private Sector. The tool of the study consisted of two parts, the first part was to detect the sources of the vocational stress among vocational teachers, and the second part was to know the compatibility strategies used by the teachers. Means, standard deviations, and percentages were counted. To explore the differences between the means; one way analysis of variance (ANOVA), and (Tuckey) were used. The results showed that the important sources of vocational stress were: the poor performance of the students on exams, the noise during lectures, lack of financial support, and the lack of development opportunities, also the results showed that the compatibility strategies used by the teachers were: positive thinking, the convection to get the best later, and the supplication and prayer, these strategies didn't vary depending on the educational authority.
Keywords: الضغوط المهنية -- التربية المهنية -- استراتيجيات التوافق